Effect of porosity gradient on mass transfer and discharge of hybrid electrolyte lithium-air batteries. (February 2022) - Zhang, Tianyu; Yu, Mingfu; Li, Jie; Li, Qiang; Zhang, Xiaochen; Sun, Hong
Highlight: The gradient electrode porosity was used in hybrid electrolyte lithium-air batteries. Comprehensive effect in the battery caused by gradient porosity was studied. Gradient porosity can increase the amount of LiOHH2 O accumulated in electrode. The reason of high overpotential caused by gradient porosity was analyzed. Abstract: The electrode porosity distribution of hybrid electrolyte lithium-air battery had a direct effect on the mass transfer inside the electrode and the accumulation of LiOH·H2 O products, which was one of the important factors affecting the specific capacity of the battery. Based on the working principle of hybrid electrolyte lithium-air battery, the macroscopic transient model of lithium-air battery was established by using the electrode dynamic equation, the mass transfer equation of porous medium and the ordinary differential equation. The changes of specific capacity, porosity distribution, oxygen concentration and lithium ion concentration under different electrode porosity gradient range were analyzed, when the discharge current density was 0.05 and 0.5 mA/cm 2 . It was found that the porosity gradient was effective to further increase the utilization of the electrode porosity and improve the oxygen transfer efficiency. However, the gradient porosity also led to the increase of battery over-potential. With discharge current density 0.5 mA/cm 2, the excessively high porosity gradient caused the significant increase of over-potential, leading to the deterioration of battery performance. This paper provided a deeper thought on the optimization of electrode pore distribution of lithium-air battery. Graphical abstract: Image, graphical abstract